Implementation of Malay Islamic Social Reform through Azyumardi Azra's Tradition and Modernity at SMA Negeri 3 Palembang - Wahyuni, Yulia; Hartati, Fitria; Fauzi, Muhammad; Mansur, Abu (Journal of English Language and Education, 2026)
Azyumardi Azra’s thought on the dialectic between tradition and modernity provides a strategic framework for understanding Islamic social reform in the Malay cultural context. He emphasizes that Islam can remain socially relevant only by preserving valuable local traditions while engaging critically with modern challenges. This study aims to analyze the implementation of Azra’s ideas in Islamic Religious Education (PAI) at SMA Negeri 3 Palembang and to examine their implications for learning practices and school culture. This research employs a qualitative approach using a case study design. Data were collected through participant observation, in-depth interviews with teachers and students, and analysis of curriculum and learning documents. The findings indicate that Azra’s thought is implemented through three main strategies. First, Malay Islamic traditions are integrated into learning as a foundation for students’ religious and cultural identity. Second, modern competencies are strengthened through the development of critical thinking, openness to diverse perspectives, and digital literacy in responding to contemporary issues. Third, pedagogical practices are transformed into dialogical learning processes that connect religious texts with students’ social realities. Overall, this study demonstrates that PAI functions not merely as doctrinal instruction, but as an effective medium of Islamic social reform that promotes religious moderation, cultural rootedness, and adaptive engagement with modernity.